2022
DOI: 10.3390/mi13020163
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Novel Medical Acoustic Sensor Based on MEMS Bionic Fish Ear Structure

Abstract: High-performance medical acoustic sensors are essential in medical equipment and diagnosis. Commercially available medical acoustic sensors are capacitive and piezoelectric types. When they are used to detect heart sound signals, there is attenuation and distortion due to the sound transmission between different media. This paper proposes a new bionic acoustic sensor based on the fish ear structure. Through theoretical analysis and finite element simulation, the optimal parameters of the sensitive structure ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In our study, the results show a good correlation between the S2A or S2E and the BP. Despite previous research proposing the determination of BP by heart sound analysis, BP estimation from the heart sound has only achieved progress in recent years [ 14 , 18 , 19 ]. Early studies suggest that a unique noninvasive BP measurement and a small range of BP variations may induce bias [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the results show a good correlation between the S2A or S2E and the BP. Despite previous research proposing the determination of BP by heart sound analysis, BP estimation from the heart sound has only achieved progress in recent years [ 14 , 18 , 19 ]. Early studies suggest that a unique noninvasive BP measurement and a small range of BP variations may induce bias [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…[23] Zhou et al proposed a new bionic acoustic sensor according to the fish ear structure. [24] They started to combined the acoustic and bionic. In this research, we reported an acoustic sensor array packaged into 3D printed ear (3DPE), which is based on piezoelectric PVDF-TrFE to identify the sound frequency and determine the location of the sound source.…”
Section: Doi: 101002/mabi202200374mentioning
confidence: 99%
“…Microelectromechanical system (MEMS)-based piezoresistive pressure sensors have wide applications in industrial construction [ 1 , 2 , 3 , 4 ], healthcare monitoring [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ], and ocean depth detection due to their high process maturity, easy sensor integration, and easy signal processing [ 12 , 13 ]. However, systematic research of the sensor performance in harsh environments is lacking, although many studies have been reported on the design and manufacturing of such piezoresistive pressure sensors.…”
Section: Introductionmentioning
confidence: 99%